Ujaran Kebencian Pada Wacana Debat Cagub Cawagub Dki Jakarta 2017dan Implementasinya Sebagai Bahan Ajar Bahasa Indonesia Di SMK - Nugraheni, Suci; , Prof. Dr. Harun Joko Prayitno, M.Hum (2017)
This research is used to identify types of hate speech in discourse of debate candidate of governor and deputy governor of DKI Jakarta 2017, to describe sign of linguistic form in discourse of debate candidate of governor and deputy governor of DKI Jakarta 2017, and to implement as teaching subject material of Indonesian language class X of senior high school. The method used in the provision of data with techniques refer, and technique of note. Technique of data analysis using method o sub-types fifth sub-type that is pragmatic method with determinant of speech. The results of this research are some form hate speech such as insult, defamation, incitement, provoking, unpleasant deeds, and spreading false news. The form of hate speech is most often found in contempt. The lingual markers of hate speech are various, such as not educating, belittling, dividing, red reporting, and so on. Hate speech in the debate discourse of governor candidate and vice governor candidate of DKI Jakarta 207 will be implemented as teaching material of Indonesian in SMK curriculum 2013 basic competence 3.13 Analyze the contents (problem/content, point of view, and argument from some parties and conclusion).